When the good go bad: Mutant NPM1 in acute myeloid leukemia. Issue 3 (May 2018) - Kunchala, Preethi; Kuravi, Sudhakiranmayi; Jensen, Roy; McGuirk, Joseph; Balusu, Ramesh
Abstract: Nucleophosmin 1 (NPM1) is a nucleolar phosphoprotein that performs diverse biological functions including molecular chaperoning, ribosome biogenesis, DNA repair, and genome stability. Acute myeloid leukemia (AML) is a heterogeneous disease, more than half of the AML cases exhibit normal karyotype (NK). Approximately 50–60 percent of patients with NK-AML carry NPM1 mutations which are characterized by cytoplasmic dislocation of the NPM1 protein. In AML, mutant NPM1 (NPM1c+) acts in a dominant negative fashion and also blocks the differentiation of myeloid cells through gain-of-function for the AML phenotype. Currently, there is limited knowledge on the gain-of-function mechanism of mutant NPM1. Here, we review the known mechanisms of mutant NPM1 in the pathogenesis of AML. We describe genetic abnormalities, the clinical significance of exon-12 mutations in the NPM1 gene, and chromosomal translocations including the recently discovered NPM1-TYK2, and NPM1-HAUS1. Also, we outline the possible therapeutic interventions for the treatment of AML by targeting NPM1. Overall, the review will summarize present knowledge on mutant NPM1 origin, pathogenesis, and therapy in AML.